Bill Aitken’s : Footloose in the Himalaya : A Saga of “Peak” Experiences - Singh, Vijay Prakash (Literary Studies, 2020)
From Buddhist Ladakh to Hindu states of Himachal Pradesh and Uttarakhand is a huge geographical stretch to traverse but being the other two Himalayan regions of North India they are significant on the traveller’s map and itinerary.